PERAN PIHAK KETIGA DALAM PENGELOLAAN PEMUNGUTAN TARIF PARKIR DI DALAM RUANG MILIK JALAN UNTUK PENINGKATAN PENDAPATAN ASLI DAERAH DI KOTA PEKANBARU - Wahyu Hidayat; Dodi Haryono; Zulwisman Zulwisman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
Based on the cooperation contract through the transportation service with a thirdparty for 10 years, namely based on "Regulation of the Minister of Finance Number 136 of2016" contained in Article 17 concerning asset management in public services for amaximum of 15 years. The formulation of the problem in this study are: 1) What is the role ofa third party in managing the collection of parking fees in the space owned by the road inPekanbaru City; 2) What are the inhibiting factors in the implementation of the managementof the collection of parking fees in the space belonging to the road by a third party; 3) Whatefforts need to be made by the Pekanbaru City Government to optimize the role of thirdparties in the management of parking rates collections in road-owned spaces in PekanbaruCity.The type of research used in this research is sociological law research. Thepopulation in this study are 1) Head of UPTD Parking Pekanbaru City TransportationService; 2) Director/Representative of PT YSM ;3) Parking attendant in a road-owned spacein Pekanbaru City; 4) Motorists who complain that paying for parking exceeds the parkingrate; 5) Chairman/Member of Commission IV DPRD Pekanbaru City. The research locationis parking inside the road owned by the city of Pekanbaru. Data collection techniques usingobservation, interviews, questionnaires and literature, with quantitative data analysistechniques.From the results of the study, it can be concluded that PT. YSM as a parking managerappointed by the Pekanbaru City Transportation Service must be able to achieve the agreedrevenue target. Some of the inhibiting factors are: 1) Parking Rates; 2) Understanding ofusers of non-cash service systems or Electronic Data Capture (EDC); 3) Payment of parkingattendant income that has not been maximized: 4) Use of parking attendant attributes andmanners in the field; 5) Parking facilities are still lacking so that the service is notmaximized; 6) Lack of supervision from the field coordinator so that the parking attendant'sincome is not maximal; 7) Pekanbaru City Transportation Service must be ready and mustalways continue to coordinate with third parties PT. YSM (Yabisa Sukses Mandiri) in orderto optimize Regional Original Income (PAD) through services; 8) A lot of road users andbusinessman who are harmed.Keywords : Third Party Role, Parking Rates, Original Local Government Revenue